Brand Equity of India as a Tourist Destination: Study of Antecedents using PLS-SEM Approach (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
India has seen dramatic growth in tourism and  slowly is emerging as one of the promising  tourist destinations. However, the potential  of the industry in terms of employment and  income generation has not been fully utilized.  An understanding of the tourist perception  and the Brand equity a destination holds  with its tourists enhances how the tourism  industry in the country shapes up. The paper  aims at contributing to the understanding of  the key psychological factors that influence  the formation of destination brand equity  perceptions among tourists. The study has  employed the Partial Least Square Structural  Equation Modelling approach for validating  the measurement and to estimate the effect of  various antecedents on the Consumer Based  Brand Equity in the context of India as a tourist  destination.
Keywords: Destination Brand Equity; Brand Awareness; Brand Image; Brand Loyalty; Perceived Quality; India